ANTIBACTERIAL ACTIVITY STUDY OF ACTIVE FRACTION FROM CHICK WEED PLANTS (Ageratum Conyzoides L.) AGAINST Bacillus Subtilis AND Vibrio Cholerae - Anggara, Ratih; Munawar, -; Elfita, - (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
The purpose of this research to determine the fractions of Chick Weed which has strong antibacterial activityÂ against bacteria test categories of Bacillus subtilis and Vibriocholerae.determine the value of the minimum in hibitory concentration(MIC) of the active fraction antibacterial Chick Weed.This research was carried out in August up to November 2016. The method used in this studyÂ were extracted by maceration, fractionation by liquid-liquid fractionation, separation by column chromatography fractions, antibacterial activity test by theKirby-Bauermethod, while the determination of minimum in hibitory concentration by dilution broth,with test bacteria Bacillus subtilis and Vibriocholerae.The data presented in tabular form based on the average value and percent.The results of this study showed that the methanol extract Chick Weed active against test bacteria Bacillus subtilis and Vibrio cholerae. Fractionation which has strong category to standard antibiotics are methanol fraction by fraction column S4.The concentration MIC1000;500;250;125;62.5;31.2515.62; 7.81 ppm. The minimum in hibitory concentration column fractions S4 to test bacteria Vibrio cholerae of 62.5 ppm gives half the antibacterial activity of the antibacterial activity of standard antibiotics streptomycin and penicillin,tetracycline while giving a quarter activity. It can be concluded that the active fraction of methanol extractisa methanol fraction by fraction column S4 to test bacteria Vibrio cholerae.Keywords: Chick Weed, Minimum Inhibitory Concentration (MIC), active compound, Bacillus subtilis, Vibriocholera.